2022
DOI: 10.3389/fonc.2022.871771
|View full text |Cite
|
Sign up to set email alerts
|

Identification of LSM Family Members as Novel Unfavorable Biomarkers in Hepatocellular Carcinoma

Abstract: BackgroundSmith-like (LSM) family members play critical roles in multiple oncologic processes in several types of malignancies. The study on LSM family members of HCC might provide new insights into the tumorigenesis and therapeutic strategies of HCC.MethodsThe clinical significance and oncologic biological functions of LSM family members were assessed through multiple bioinformatics methods and in vitro studies. The potential correlation between LSM family members and tumor immunity was also investigated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…However, there is lack of studies on the role of LSM5 and LSM8 in tumors. Recent study revealed a risk score system consisting of LSM5 and identified it as a reliable predictive biomarker for hepatocellular cancer (28). So it is challenging but greatly significant to explore the underlying molecular mechanism about why LSM5 and LSM8 could be potential biomarkers for chemoresistant GC patients, we firstly analyzed the GO enrichment and KEGG annotation in GC.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is lack of studies on the role of LSM5 and LSM8 in tumors. Recent study revealed a risk score system consisting of LSM5 and identified it as a reliable predictive biomarker for hepatocellular cancer (28). So it is challenging but greatly significant to explore the underlying molecular mechanism about why LSM5 and LSM8 could be potential biomarkers for chemoresistant GC patients, we firstly analyzed the GO enrichment and KEGG annotation in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, LSM2 mRNA level was identified as an independent risk factor for shorter OS and PFS in SKCM. Similarly, some previous studies revealed that high LSM2 mRNA expression was significantly associated with poor OS in patients with BRCA [ 29 ] and HCC [ 31 ]. Thus, LSM2 may be an oncogene.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, in the BioGPS database, LSM2 was found to be highly expressed in cutaneous melanoma cells compared to normal skin cells. Markedly upregulated LSM2 mRNA expression was also found in breast cancer (BRCA) [ 29 ], pancreatic ductal adenocarcinoma (PDAC) [ 30 ], and hepatocellular carcinoma (HCC) [ 31 ]. Germline variants and somatic mutations of LSM2, which belong to mRNA splicing-related genes, have been confirmed to be high-risk factors for lung cancer [ 21 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the main factors participating in DNA damage induced by oxidative stress [15]. Heretofore, the research on the function of LSM12 in human malignant tumors is still very limited [16][17][18]. Here, we demonstrated that LSM12 is involved in cytopathologic and tumorigenic functions during CRC development through the regulation of CTNNB1 protein stability and CTTNB1-LEF1-TCF1 transcriptional complex formation.…”
Section: Discussionmentioning
confidence: 78%